KONTEN ANALISIS AKUN INSTAGRAM @advanindonesia DALAM MEMPROMOSIKAN PRODUK SMARTPHONE ADVAN GX - Muhammad Hidayattuloh; Sonson Nurusholih; Iman Sumargono (Universitas Mercu Buana, 2022)
Advan is one of the local mobile phones that already has a good brand and can be accepted by the Indonesian market. Various products have been produced by Advan, one of which is the Advan GX which has a number of unique products in terms of camera specifications, ram, battery capacity, and a good capable processor and is claimed to be able to run various applications including games without a hitch. Like other mobile phone brands, Advan has an official Instagram social media account @advanindonesia which communicates various products, including Advan GX. Looking at the @advanindonesia account until August 2021, Advan GX got a good response from the community. This can be seen from the high number of likes and comments on Instagram posts about these products. Where the number of likes and comments on this product has reached over 1,000 likes and comments above 100 in several posts. This number is inversely proportional to other Advan products such as the Advan G5 Elite which only got 451 likes and 83 comments on one of its posts. In addition to the high number of likes and comments, a number of Instagram posts that support the promotion of these products communicate their uniqueness both in terms of cellphone specifications, social media skills, and the ability to run game applications. This study examines Instagram posts containing promotions of Advan GX products on the Instagram social media account @advanindonesia based on content analysis methods that calculate the frequency of occurrence of design elements, including composition, use of letters/typography, and photography. In supporting the research, visual communication design theory is used as a supporting tool. The results of this study show that there is a tendency in the use of symmetrical compositions, the use of various sans seris and bold letters to emphasize the uniqueness of the product, as well as the use of photography that illustrates products that are in accordance with their uniqueness.